2008
DOI: 10.1111/j.1572-0241.2008.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Calprotectin Predict Relapse Risk in Inflammatory Bowel Disease?

Abstract: Measuring calprotectin may help to identify UC and colonic CD patients at higher risk of clinical relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 26 publications
5
115
1
6
Order By: Relevance
“…8,15 Increased FC concentrations are associated with an increased risk of clinical relapse. [16][17][18][19][20][21] Its value in the post-operative setting, however, is uncertain.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…8,15 Increased FC concentrations are associated with an increased risk of clinical relapse. [16][17][18][19][20][21] Its value in the post-operative setting, however, is uncertain.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The 71 patients with Crohn's disease were checked for the erythrocyte sedimentation rate and CRP every 6 weeks, and the relapse risk in the short term has been found to be 8 times higher in those with a sedimentation rate >15 mm and CRP >20 mg/L. The sensitivity of the fecal calprotectin is 68% to 100% and the specificity is 30% to 67% in determining the relapse for patients with clinical and endoscopic remission (6,11,12). The colonoscopy should be performed every 1 -2 years for surveillance against tumor development in patients having Crohn's colitis in 8-10 years after the diagnosis of the disease for the patients with complete colonic (13).…”
Section: Resultsmentioning
confidence: 99%
“…Data support its use in differentiating irritable bowel syndrome (IBS) from inflammatory bowel disease (IBD), 1,[22][23][24][25] evaluating abdominal discomfort, 26 reducing the need for endoscopy in suspected IBD, 27 assessing treatment response in IBD, 14,15,[28][29][30] predicting relapse in IBD 7,8,[10][11][12][13] and predicting mucosal healing in IBD. 3,6,30,31 Indeed at our own institution, the monthly FC workload has increased from 50 samples a month in January 2007 to over 1000 per month in August 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating CD relapse rates have reported that FC concentration may be a less reliable predictor of relapse in ileal CD. 11,12 We included 15 patients of this subtype in our analysis. When analysed separately we discovered that both consistency and case reliability were lower for these patients than for the whole study group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation